Exploring the antecedents of business strategies in Bancassurance sector of Pakistan - Iqbal, Muhammad Nawaz; Omercic, Jasmin (International Research and Publishing Academy, 2024)
t is critical to determine the precursors of successful business strategies in the everchanging Pakistani Bancassurance market. The urgent need to comprehend the variables influencing strategic decision-making in this industry is addressed by this study. Through an exploration of the complex interactions between several internal and external factors, This study seeks to evaluate the fundamental factors that impact strategic decisions in the life insurance industry. This research's rationale stems from the realization that effective business plans are a result of organizational capacity and strategic foresight in addition to market circumstances. Comprehending these precursors is of paramount importance for scholars and professionals in the sector alike, as it can furnish invaluable discernments into the ways in which Bancassurance enterprises can more adeptly maneuver the intricate commercial landscape. The research is qualitative in nature. Thematic analysis have been applied as a tool to analyze the transcribe data obtained through interviews. The themes obtained through interviews are Business productivity through distribution network, Efficiency in business communication protocols, Enhancement in bank’s consumer market share, Increase of capital adequacy value of bank’s market share, Reshaping Bancassurance partners business strategy in consumer market Banks can effectively diversify their product and service offerings, thereby increasing revenue streams, optimizing resource use, and perhaps strengthening their market positions, by working together with Bancassurance.